The Trust Imperative: Conceptualizing the Dynamics of Trust and Distrust in Parent‐Professional Collaboration. Issue 5 (16th January 2023) - Matthiesen, Noomi; Cavada‐Hrepich, Paula; Tanggaard, Lene
Abstract: This article develops a conceptual framework of the dynamics of trust between parents and professionals in early childhood education and care. In contemporary Western society, the heightened risk awareness with respect to early childhood has led to an increased focus on the collaboration between home and daycare. Mutual trust is a core aspect of this collaboration, resulting in a trust imperative. Drawing on Knud Eilar Løgstrup, Noomi Matthiesen, Paula Cavada‐Hrepich, and Lene Tanggaard argue here that trust is a spontaneous, relational phenomenon rooted in practice and emerging in a normatively structured order. They develop a conceptual framework of trust that has two dimensions: a basic dimension and a competence dimension . The basic dimension is connected to the willingness of the other to do what is good and right according to the normative order, while the competence dimension has to do with the ability to do so. The authors contend that, while trust is a spontaneous and sovereign phenomenon outside of individuals' control, parents and professionals in daycare perform in ways that are recognized as more or less trust‐ worthy . They also perform in ways that signal they are trust‐ ful . However, these conscious performances can paradoxically reduce the possibility of spontaneous trust.